HUBUNGAN ANTARA USIA, AKTIVITAS FISIK, DAN INDEKS MASSA TUBUH DENGAN KEJADIAN NYERI PUNGGUNG BAWAH PADA ANGGOTA TNI AD DI RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO PERIODE APRIL 2014 - Levi Aulia Rachman, (2014)
Low Back Pain (LBP) based on several risk factors, such as age, bad fitness, heavy physical activity, smoking, sitting and driving for hours, bent position then rotate back, and extreme sports. Army has a duty related to heavy physical activity are highly correlated with the incidence of LBP. LBP is often encountered in daily life and an estimated 70-85% of the world population have experienced. The prevalence in some hospitals in Indonesia ranges between 3-17%. The aim of This study isto determinethe relationship between age, physicalactivity, and body mass index (BMI) withlow back painona memberof the army. The population is all the army with a sample research as much as 45 people are consecutive sampling, the data by using a GPAQ questionnaire. Data was analysis by Chi-Square test resulted there is relation between physical activities (p=0.027) and BMI (p=0.020) with LBP incidence, but there isn't relation with age (p=1.000) with LBP incidence.